Methodology for the systematic investigation of the hygrothermal-mechanical behavior of a structural epoxy adhesive. (March 2022) - Sander, S.; Meschut, G.; Kroll, U.; Matzenmiller, A.
Abstract: A methodology is presented for the systematic determination of moisture absorption behavior of a structural epoxy adhesive in order to investigate the influence of humidity on the strength, fracture energy and fracture strain of adhesively bonded joints subjected to monotonic quasi-static loading. The first step consists of a preliminary weighting test to assess the parameters of the Fick diffusion model for the adhesive at hand by means of a thin disc made of cured adhesive bulk material. Numerical simulations verify the applied assumption of one-dimensional diffusion. It turns out that the adhesive disc is not thin enough in order to achieve reasonable testing times up to saturation for the complete characterization of moisture absorption. Therefore, the specimen thickness is systematically reduced. In the second step, the diffusion behavior of the adhesive is characterized. In order to get a homogeneous humidity level within the whole specimen, several adhesive discs are exposed to a reference temperature and humidity, according to the prior dimensioning. This novel procedure of preconditioning allows for a homogeneous and, thus, well-defined initial state of water content in the specimens. From this state, the discs are exposed to various environmental conditions, which include different temperatures and relative humidity of the surrounding moist air. It is observed that moisture saturation primarily depends on the relative humidity, while the diffusion coefficient depends on temperature for this epoxy adhesive. Fick's model of diffusion is applied to represent the moisture uptake of the adhesive at hand, whereby the initial state of water saturation after preconditioning is taken into account. Based on the findings in step 1 and 2, the influence of moisture is determined in step 3 on the strength, fracture energy and elongation at rupture of adhesively bonded joints. Thick adherend shear specimens (TASSs) are preconditioned in order to achieve a variety of homogeneous moisture states in the corresponding adhesive layer. After preconditioning, quasi-static tensile tests of the TASSs are carried out at various temperature levels. The experimental results reveal that the strength and fracture energy of the TASS degrades progressively with higher temperature and increased humidity.